2018
DOI: 10.1097/iae.0000000000001591
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy for Macular Disorders Associated With Lamellar Macular Hole Epiretinal Proliferation

Abstract: Lamellar macular hole with LHEP showed poorer visual outcomes compared with those with highly reflective epiretinal membranes. Lamellar macular hole with LHEP showed a greater chance of ellipsoid zone disruption. These findings may explain the wide variability of visual outcomes previously reported after vitrectomy for LMH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 14 publications
10
73
1
1
Order By: Relevance
“…The visual performance of eyes with LMH with or without LHEP did not differ at the end of our follow-up, either with observation or after surgery. The similarity concerning BCVA progression within all groups matches the results obtained in similar studies on LHEP [13, 17], except for a recent study that linked LHEP to a worse visual prognosis [10]. As has already been reported [5, 13], LHEP are described as a yellowish pigment on color fundus photography, the soft consistency of which turns the ERM/ILM peeling into a more difficult task when compared to “conventional ERM.”…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The visual performance of eyes with LMH with or without LHEP did not differ at the end of our follow-up, either with observation or after surgery. The similarity concerning BCVA progression within all groups matches the results obtained in similar studies on LHEP [13, 17], except for a recent study that linked LHEP to a worse visual prognosis [10]. As has already been reported [5, 13], LHEP are described as a yellowish pigment on color fundus photography, the soft consistency of which turns the ERM/ILM peeling into a more difficult task when compared to “conventional ERM.”…”
Section: Discussionsupporting
confidence: 84%
“…LMH management is still a matter of debate, but in asymptomatic LMH patients, observation complemented with serial OCT follow-up is usually the preferred approach, while in patients complaining of metamorphopsia or visual acuity changes, a surgical approach is to be considered in order to restore both foveal anatomy and visual performance [4, 5]. However, studies have demonstrated varying anatomical and visual outcomes after surgery [6-9] that may in part be explained by lamellar hole-associated epiretinal proliferations (LHEP) [10], which are related with a minimal traction component compared to typical hyperreflective epiretinal membranes (ERM).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rationale is to release vitreomacular adhesions by removing the ERM and ILM, facilitating re­establishment of the regular foveal profile. Some surgeons use temporary intravitreal tamponade, such as air or gas, and instruct the patient to maintain a prone position postoperatively [71-74, 76-80]. Others have demonstrated that intravitreal tamponade and postoperative prone positioning are not crucial for the surgical success [3, 75, 81, 82] (Table 1).…”
Section: Surgical Treatment Of Lmhmentioning
confidence: 99%